TINDAK TUTUR ILOKUSI DALAM KUMPULAN CERPEN GALUH PASAR TERAPUNG KARYA ALIANSYAH JUMBAWUYA DAN HATMIATI MASY’UD - NFN, Jahdiah (Balai Bahasa Provinsi Papua, 2019)
Illocution speech act is a speech act that has function to state something and used to do smething. The Promlem whin which is discussed in study is what kind of illocution that used in a colecction of Galuh Pasar Terapung by Aliansyah Jumbawuya and Hatmiati Masy’ud. The aim of this study is to descirbe the type of illucotion speech act in collection of Galuh Pasar Terapung short. This study uses two approaches, they are theoritical approach and methodological approach,. The data analyze which is used in this study is analytical content technique. The result show that there are five illocution speech act in a colletion of Galuh Pasar Terapung short strory, they are representative, commisive, directive, and declarative.